DUKUNGAN SOSIAL MENINGKATKAN KUALITAS HIDUP LANSIA : REVIEW ARTICLE - May Dwi Yuri Santoso (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Elderly is one of the developmental periods characterized by a decrease in physical, psychological and social functions. This decrease in function can reduce the quality of life of the elderly. To improve the quality of life of the elderly a social support is needed. The social support aims to help the elderly to fulfill their life needs. The purpose of this article review is to review various articles regarding social support for the quality of life of the elderly so that it can be used as information data so that the elderly do not experience problems of lack of attention or affection, feeling lonely, depressed and feeling useless, thus fulfilling their life needs. The method used is a scientific electronic bibliographic database of articles published through Google Scholar as many as 2,680,000 articles and from Google Scholar 6,320 articles, then 10 articles are selected. The results of a review of 10 articles that have been chosen state that social support improves the quality of life for the elderly. Social support is defined as the existence or presence of someone who is trustworthy, understanding, caring and loving, from the closest people such as children, family, and society that are needed by the elderly to live the rest of their lives because it is a support system for the elderly to be active amid the limitations experienced. Key words: Social Support, Quality of Life, Elderly